All Days 2013
DOI: 10.4043/24068-ms
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Equations of Shear Wave Velocity for Bay of Campeche Clay

Abstract: One of the most important soil parameters required in the analyses of the piles of oil platforms subjected to lateral earthquake loading is the shear wave velocity (V S ) of the soil. Since in-situ measurements of V S is part of the scope of work of a limited amount of platform sites, there is the need to develop site specific correlations to estimate V S based on basic soil properties. To cover this need a database with in-situ measurements of V s and basic soil properties of clay has been established. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…This was confirmed by the analysis of a number of landslides occurring without external causes and by laboratory data (Bjerrum 1954). Empirical correlations between Vs and undrained shear strength determined in triaxial or direct shear tests and with empirical interpretations of geotechnical in situ testing have been established (Dickenson 1994;Andersen 2004;Taboada et al 2013). Specific correlations have also been proposed for Norwegian clays (NGI 2015;L'Heureux & Long 2017).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…This was confirmed by the analysis of a number of landslides occurring without external causes and by laboratory data (Bjerrum 1954). Empirical correlations between Vs and undrained shear strength determined in triaxial or direct shear tests and with empirical interpretations of geotechnical in situ testing have been established (Dickenson 1994;Andersen 2004;Taboada et al 2013). Specific correlations have also been proposed for Norwegian clays (NGI 2015;L'Heureux & Long 2017).…”
Section: Introductionmentioning
confidence: 77%
“…Bjerrum (1954) showed that leaching could cause a shear strength reduction in the order of 40 per cent from the original material and, by collecting different Norwegian clay samples, observed relatively constant density values which showed no particular correlation with material sensitivity. Depending on the proposed correlations (Dickenson 1994;Andersen 2004;Taboada et al 2013;NGI 2015;L'Heureux & Long 2017) between Vs and undrained shear strength different ranges of reduction could be attended in the shear wave velocity from non-leached clay to quick clays.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
“…In this study, four relatively recent published correlations are analyzed using the local CPTu data: two generic correlations (Robertson, 2009;Tong et al, 2018), and two for specific soil types (Long & Donohue, 2010;Taboada et al, 2013). This selection was based on a preliminary fit analysis for the generic correlations and for the correlations with similar offshore conditions for the specific soil type.…”
Section: Previous Published Cptu-v S Correlationsmentioning
confidence: 99%
“…6 was chosen for further analysis. Taboada et al (2013) analysed P-S logging data for the Bay of Campeche, Mexico, aiming to evaluate the geohazards involved in offshore petroleum exploration. Their study can be directly related to the present work, as it was developed under similar site conditions.…”
Section: Soil-type Specific Correlationsmentioning
confidence: 99%
See 1 more Smart Citation